A case of recurrent takotsubo-like cardiomyopathy associated with pheochromocytoma exhibiting different patterns of left ventricular wall motion abnormality and coronary vasospasm: a case report. Issue 4 (25th May 2020) - Sato, Koichi; Takahashi, Jun; Amano, Keiko; Shimokawa, Hiroaki
Abstract: Background: Takotsubo-like cardiomyopathy associated with pheochromocytoma (Pheo-TTS) is a recognized but uncommon disorder. While Pheo-TTS might more often recur and the pattern of left ventricular (LV) wall motion abnormality is more diverse compared with primary TTS, it remains to be elucidated whether coronary functional abnormalities are also involved. Case summary: A 50-year-old woman was referred with a chief complaint of transient chest pain, dyspnoea, and paroxysmal thyroid swelling that usually developed after meals. In the past, she had been admitted to emergency rooms three times due to pulmonary oedema following the above attacks. Serial cardiac catheterizations showed normal coronary arteries and morphologically different types of LV dysfunction each time; apical LV ballooning at the first, basal LV ballooning at the second, and diffuse LV hypokinesis at the last admission. Acetylcholine (ACh) provocation testing for coronary vasospasm was negative at the second admission. During hospitalization in our department, abdominal ultrasonography for screening detected a right adrenal mass and the urinary normetanephrine level was increased. The adrenal tumour was urgently removed surgically and finally she was diagnosed as having norepinephrine-secreting pheochromocytoma. Acetylcholine testing was again performed just after the operation, showing both epicardial and microvascular coronary spasms. Since the operation, she has been free of symptoms. Importantly, ACh testing at 1-year follow-up showed that epicardial spasm was no longer noted, whereas coronary microvascular spasm persisted. Discussion: Adrenal pheochromocytoma could cause recurrent attacks of catecholamine surges with different patterns of LV dysfunction, where coronary vasospasm may also be involved along the coronary arteries.